A Research Agenda for Peace and Tourism - Farmaki, Anna (My University, 2024)
This highly prescient Research Agenda critically examines the delicate intersection of peace and tourism and proposes further research in order to explore how tourism may contribute to peace or, conversely, hinder the peacebuilding efforts of destinations in conflict. Chapters discuss tourism as a peace-builder, the acceptance of dark tourism, a gender approach to peace through tourism, and corporate social responsibility as a contributor to peace in conflict-ridden situations.
Keywords: Peace; Conflict; Reconciliation; Destinations; Research Agenda